2009
DOI: 10.1603/022.038.0134
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Variation and Range Expansion in Western Bean Cutworm (Lepidoptera: Noctuidae): No Evidence for a Recent Population Bottleneck

Abstract: The western bean cutworm, Striacosta albicosta (Smith) (Lepidoptera: Noctuidae), is a pest of both corn and dry bean crops. At the beginning of the 21st century, the species began to extend its range out of the Great Plains, eastward through the Corn Belt. This rapid range expansion is remarkable because the species distribution had been stable for at least the previous half century, despite the apparent abundance of suitable habitat (i.e., cornfields) immediately to the east. We hypothesized that if the weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…It is possible that a genetically diverse group, perhaps from multiple locations, colonized the new territory. Like Miller et al (2009) we conclude that as there is no evidence of a bottleneck effect; therefore, it is unlikely that S. albicosta evolved the ability to overcome some barrier, but rather that there was a previous barrier to population expansion that is no longer present.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…It is possible that a genetically diverse group, perhaps from multiple locations, colonized the new territory. Like Miller et al (2009) we conclude that as there is no evidence of a bottleneck effect; therefore, it is unlikely that S. albicosta evolved the ability to overcome some barrier, but rather that there was a previous barrier to population expansion that is no longer present.…”
Section: Discussionsupporting
confidence: 59%
“…Eastern locations also do not exhibit more genetic isolation from western locations than western locations do from one another. Miller et al (2009) came to a similar conclusion by analyzing differences in the NADH dehydrogenase gene in the mitochondrial DNA of four subpopulations of S. albicosta from Wyoming, Nebraska, and Iowa. Their study revealed no signiÞcant heterogeneity between subpopulations, and they rejected the hypothesis that S. albicosta subpopulations in the east are subject to a bottleneck effect.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In recent years, significant western bean cutworm infestations have been observed in corn beyond the previously described range in the west-central United States (Miller et al 2009). S. albicosta has been documented north to Iowa and southern Minnesota, east to Massachusetts, and south into Mexico (O'Rourke and Hutchison 2000, Rice 2000, Michel et al 2010, PSU Pestwatch 2014.…”
mentioning
confidence: 86%